A Conceptual Framework of How Meeting Mindsets Shape and Are Shaped by Leader–Follower Interactions in Meetings. (May 2022) - Gerpott, Fabiola H.; Kerschreiter, Rudolf
In this conceptual paper, we define a person's meeting mindset as the individual belief that meetings represent opportunities to realize goals falling into one of three categories: personal, relational, and collective. We propose that in alignment with their respective meeting mindsets, managers use specific leadership claiming behaviors in team meetings and express these behaviors in alignment with the meeting setting (virtual or face-to-face) and their prior experiences with their employees. Employees' responses, however, are also influenced by their meeting mindsets, the meeting setting, and prior experiences with their managers. The interplay between managers' leadership claiming behavior and their employees' responses shapes leader–follower relations. Embedded in the team context, the emerging leader–follower relations impact the meaning of meetings. We outline match/mismatch combinations of manager–employee meeting mindsets and discuss the influence that a manager and employee can have on each other's meeting mindset through their behavior in a meeting.Plain Language Summary Have you ever had the experience of entering a team meeting and quickly realizing that your idea of how the meeting conversation should be approached did not align with your boss's understanding of the meeting purpose? This is indeed a common experience in meetings between managers and their employees. While we understand much about the communication dynamics that occur in meetings, we know less about what motivates people to communicate in certain ways in meetings. In this conceptual paper, we classify people's understanding of meetings as being driven by one of three purposes: [1] to strategically position and promote themselves (which reflects a personal meeting mindset), [2] to shape collaborations and to ensure reciprocation (which reflects a relational meeting mindset), or [3] to strengthen the team identity and increase the willingness to go the extra mile for the team (which reflects a collective meeting mindset). Meeting mindsets shape how people enact their leader or follower role in meetings—that is, how a manager exhibits leadership and how employees react. However, managers' and employees' meeting mindsets may not necessarily match, which can trigger tensions and may ultimately change the way in which managers or employees define the meaning of meetings. Our research helps managers to comprehend the reasoning behind their own and other people's meeting behavior and may promote reflection on one's leadership approach, particularly in a team meeting context. It can also help employees to grasp the power they can have in terms of actively shaping their managers' meeting mindsets.